Pengetahuan dan Sikap Manusia Terhadap Isu Lingkungan - Alam, Ashary; Ardi, Muhammad; Asrib, Ahmad Rifqi (Pascasarjana Universitas Negeri Makassar, 2018)
Environmental issues are problems that arise from the results of greedy human activities in exploiting nature. Many environmental issues have made humans vulnerable to disasters. The utilization of energy resources carried out by humans today results in air pollution, the greenhouse effect, and global warming. The environment becomes degraded due to human activation, a degraded environment will only have a negative impact on human life. This article discusses human knowledge and attitudes towards environmental issues. Environmental knowledge is general knowledge about facts, concepts, or relationships related to the surrounding environment and its ecosystem. Every human being has different environmental knowledge because it is influenced by factors of education, experience, information, the area of residence. Knowledge of the environment that humans have will support their environmental attitudes and behavior. Every environmental issue that occurs will bring up two kinds of attitudes in the community, namely positive and negative attitudes. Every attitude possessed by humans will determine what steps they will choose in facing environmental issues, such as turning off lights, turning off electronic equipment, choosing vehicles with minimal emissions.